The Analysis of Nonstationary Time Series Using Regression, Correlation and Cointegration - Søren Johansen (Contemporary Economics, 2012)
There are simple well-known conditions for the validity of regression and correlation as statistical tools. We analyse by examples the effect of nonstationarity on inference using these methods and compare them to model based inference using the cointegrated vector autoregressive model. Finally we analyse some monthly data from US on interest rates as an illustration of the methods.
Keywords: C32; 330; regression; correlation; cointegration; model based inference; likelihood inference